O documentário de Paulo Gil Soares na Caravana Farkas : vozes, personagens e cultura popular - Cury, Joyce Felipe (Universidade Federal de São Carlos, 2015)
This research takes a look at the eight documentaries directed by Paulo Gil Soares between 1960 and 1970 in the experience that became known today as Caravana Farkas, all of them made in northeastern Brazil: Memória do cangaço (1965), Erva Bruxa (1969-70), A morte do boi (1970), A mão do homem (1969-70), Jaramataia (1970), O homem de couro (1969-70), Vaquejada (1970) e Frei Damião: trombeta dos aflitos, martelo dos hereges (1970). It´s about short and medium-length films that were inserted in a project which had the intention to “bring Brazil to the Brazilians” – in vogue in the context of the Cinema Novo – and it was attended by filmmakers who experienced a very singular production, in which it is perceived a share political views and, especially, aesthetics and thematic options in the documentary field. By trying to step away from the generalization about that experience, which is sometimes present the literature on Brazilian cinema, we will point out the distinctive features of the eight Paulo Gil Soares movies. It's our purpose to outline the features of this filmmaker's "voice" in Caravana Farkas and thus differentiate him from other directors of the same experience. For this purpose, in the filmic analysis that follow, we will focus in three relevant aspects to the aesthetic and discursive constructions of his documentaries: the activated voices, the way the characters are portrayed and the appropriation from folk culture.
Keywords: Documentário brasileiro; Caravana Farkas; Paulo Gil Soares; Voz; Personagem; Cultura popular; Voice; Folk culture; Character; Brazilian Documentary; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO